Pengaruh Dimensi Konsekuensi Religiusitas dan Sanksi Perpajakan Terhadap Kepatuhan Dalam Perpajakan - Intan Nur Jannah; Indriyana Puspitosari (EBBANK, 2018)
This study aimed to analyze the influence of religiosity and tax sanctions for compliance in taxation. In this study, the research data obtained by distributing questionnaires survey method set to 100 individual tax payer on KPP Pratama Boyolali. The data obtained in this study were analyzed using the Multiple Linear Regression Analysis. The variables used in the research studies using two variables: the independent variable (X) and the dependent variable (Y). For the independent variable (X) include consequences on Religiosity and Sanctions Taxation, while the dependent variable using a variable in the Tax Compliance. The results showed that the variables consequences on religiosity and sanctions taxation positive and significant impact on Compliance in Taxation. Thus we can conclude an individual taxpayer on KPP Pratama Boyolali persuming their religiosity and sanctions taxation can increase or decrease their tax compliance.